Effects of sugars and aminooxyacetic acid on the longevity of pollinated Dendrobium (Heang Beauty) flowers - Chandran, S.; Toh, C.L.; Zuliana, R.; Yip, Y.K.; Nair, H.; Boyce, A.N. (2006)
The vase life of detached pollinated Dendrobium (Heang Beauty) orchids are affected by loss of energy source and the production of pollination-induced ethylene. The physiological changes that follow these two events are discoloration, thinning of petals and hyponasty. In order to circumvent this problem, individual detached pollinated Dendrobium (Heang Beauty) fl owers were treated with solutions containing different concentrations of sucrose or glucose, Aminooxyacetic acid (AOA) and a combination of sugars and AOA. Discolouration, petal thickness and hyponasty were observed and data was recorded daily. Weight loss of fl owers and pH of all solutions were also measured daily. Results showed that the best treatment solution in extending the longevity of the fl owers were solutions containing 4 sucrose + 0.5mM AOA. Flowers held in this treatment also showed a delay in discoloration, thinning of petals and hyponasty. The inclusion of AOA into solutions resulted in low pH and contributes to better water uptake and delayed turgor loss in flowers.